Carbon markets: a historical overview. (8th February 2013) - Calel, Raphael
Abstract: The global carbon trade has in a short space of time grown into a market worth over 175 billion a year. The history of carbon markets is a great political success story, and today they form an integral part of international climate change policy. Yet we only have a very limited understanding of how well these markets work in practice. Studying the incoming evidence and piecing it together with past emissions trading experiences can teach us a lot about how carbon markets work, and how they can fail. This article reviews the history of emissions trading and the rise of carbon markets as a basis for better understanding what is happening now. Viewing these markets in a historical light reveals that many of the current problems have precedent, and that we are perhaps not learning enough from past experiences. If carbon market policies were more geared toward systematic evaluation, and more open to incorporating past lessons into new policy, carbon markets would stand a greater chance of helping achieve the transition to a low‐carbon economy. WIREs Clim Change 2013, 4:107–119. doi: 10.1002/wcc.208 This article is categorized under: The Carbon Economy and Climate Mitigation > Policies, Instruments, Lifestyles, Behavior